2023
DOI: 10.1093/jsxmed/qdad037
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of systemic inflammatory response and oxidative stress in erectile dysfunction through multi-inflammatory index: a prospective cross-sectional analysis

Abstract: Background Systemic inflammation and oxidative stress increase the possibility of erectile dysfunction (ED) through a coordinated response to vascular endothelial damage. Aim The study aimed to evaluate the status of oxidative stress and systemic inflammation in ED. Methods The analysis was a prospective, cross-sectional, single-center study. The study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Therefore, it was expressed that MII could be useful in the early determination of poor prognosis in COVID-19. In other studies, the diagnostic efficiency of MII was showed in patients with degenerated intervertebral disc [27] and erectile dysfunction [28] as well.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, it was expressed that MII could be useful in the early determination of poor prognosis in COVID-19. In other studies, the diagnostic efficiency of MII was showed in patients with degenerated intervertebral disc [27] and erectile dysfunction [28] as well.…”
Section: Discussionmentioning
confidence: 83%
“…11,12 Erectile function has been shown to worsen with systemic in ammation, thereby providing a possible explanation for our ndings. 13 These heightened in ammatory biomarkers, and their relationship to ED, display that long COVID may cause endothelial damage.…”
Section: Discussionmentioning
confidence: 99%
“…ED is a disease with a multifactorial pathogenesis. A prospective cross-sectional study showed higher levels of inflammation and oxidative stress in the ED group [ 11 ]. A study conducted in dialysis patients showed that low levels of systemic inflammation was significantly associated with the severity of ED [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors associated with ED are numerous, including age, cardiovascular disease, hypertension, body mass index (BMI), diabetes, lack of exercise, hyperhomocysteinemia and smoking [ 7 10 ]. Inflammation and endothelial dysfunction are important factors that promote ED [ 11 , 12 ]. Inflammation not only affects endothelial cells but also contributes to the pathogenesis of metabolic syndromes, all of which promote ED [ 9 ].…”
Section: Introductionmentioning
confidence: 99%